2018
DOI: 10.1182/blood-2018-99-118325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Splenectomy before Transplantation on β-Thalassaemia Major with Matched Sibling and Unrelated Hematopoietic Stem Cell Transplantation

Abstract: Purpose:Splenectomy can improve the quality of life of patients with β-thalassaemia major to some extent, but also increase some unpredictable risk.In order to understand the effects of splenectomy before transplantation on hematopoietic stem cell transplantation reconstruction time, infection, graft versus host disease and hepatic veno-occlusive disease of matched sibling and unrelated hematopoietic stem cell transplantation, the following studies were conducted. Methods:A retrospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Noticeable, the proportion of late deaths was more in the splenectomized group (50%) than in the nonsplenectomized group (14.3%), and encapsulated bacterial sepsis was one of the causes of late death in splenectomized patients in our study. There was no significant impact of splenectomies on the incidences of acute or chronic GvHD, or of VOD, which was consistent with other reports on β‐thalassemia major 5,8 . We also did not observe any long‐term complications, such as thrombosis or restrictive pulmonary function, among the splenectomized patients in our study, which corresponded with the findings of the previous study 5 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Noticeable, the proportion of late deaths was more in the splenectomized group (50%) than in the nonsplenectomized group (14.3%), and encapsulated bacterial sepsis was one of the causes of late death in splenectomized patients in our study. There was no significant impact of splenectomies on the incidences of acute or chronic GvHD, or of VOD, which was consistent with other reports on β‐thalassemia major 5,8 . We also did not observe any long‐term complications, such as thrombosis or restrictive pulmonary function, among the splenectomized patients in our study, which corresponded with the findings of the previous study 5 .…”
Section: Discussionsupporting
confidence: 92%
“…Our splenectomized patients had significantly faster neutrophil engraftments, despite their numbers of CD34 + and TMN cells not being significantly different from those for the nonsplenectomized patients. This observation is consistent with earlier studies of β‐thalassemia major, Gaucher's disease, myelofibrosis, and chronic myeloid leukemia patients, which demonstrated that a splenectomy before an HSCT could alter engraftment kinetics and enhance neutrophil engraftment 5‐8,14‐17 . However, and in contrast to a previous report on β‐thalassemia major, 5,7 our study found that the time to red blood cell transfusion independence, platelet engraftments, and transfusion requirements during transplant period were not significantly different.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation